ANALISIS PREFERENSI PETANI TERHADAP KARAKTERISTIK TEKNOLOGI PADI LADANG (KASUS DI KABUPATEN LAMPUNG TENGAH DAN LAMPUNG SELATAN, PROPINSI LAMPUNG) - SUCI INDRANINGSIH, KURNIA; K. SEJATI, WAHYUNING; WAHYUNI, SRI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Rice is important role as Indonesian main food. It takes share 25-30% from total household expenses. But, government programs still can’t fulfill farmers’ need, because the dissemination of the program is still using delivery system approach. Effort to fulfill the needs is by an acquisition system that pointed toward farmers to look for technology from the information source. The main characteristic of this system are: (1) bottom up approach, (2) horizontal hierarchy, and (3) participated and interactive technology transfer. This paper aims to explain: (1) technology classification used by farmers; (2) Farmers’ preference and reason to choose appropriate technology, according to technique, economic, social-culture, and sustainable aspects; and (3) technology characteristic used by farmer to optimize the achieved production and productivity. The results of this study indicated that the local and adaptive technology used by farmers was conducted by cultured approach. Technology applied by farmers can be classified: (1) local technology (39-77%), adaptive technology (20-23%); and advanced technology (3-38%). The priority scale of rice technology criteria preferred by farmers was economic (0.33), sustain (0.32), technique (0.23) and social-culture (0.12). Component technology prioritized was fertilization, disease protection, and post harvest, with priority scale of each component 0.24; 0.19; and 0.13. This study was also recommended that to increase rice production, “embung” technology could be introduced to the farmers, besides organic farming must be encouraged. Applied technology is gained based on philosophy, tradition, and other social aspect, which becomes farmer’s motivator.
Keywords: Rice, Preference, Technology